Biological activities of Curcuma purpurascens BI. Rhizome extract using in vitro and in vivo models / Elham Rouhollahi - Elham, Rouhollahi (2016)
Curcuma purpurascens BI. is a medicinal plant from the Zingiberaceae family, which is widely used as a spice and in folk medicine for the treatment of wounds, scabies, itching, fever, cough and boil. In this study, chemopreventive properties of dichloromethane and hexane extracts of C. purpurascens BI rhizome (DECPR and HECPR) on azoxymethane-induced colonic aberrant crypt foci (ACF), gastroprotective and wound healing potential in rats were been evaluated. The acute toxicity test of DECPR and HECPR in rats, carried out in two doses, i.e. 2 and 5 g/kg, showed that these two plant extracts were safe even at a high dose (5 g/kg). DECPR apoptosis-inducing effect was investigated against HT-29 colon cancer cell line utilising a bioassay-guided approach. The chemoprotective experiment was performed in five groups of rats: negative control, positive cancer control, DECPR (250, 500 mg/kg) and reference drug (5-fluorouracil) group. Methylene blue staining of colon specimens showed that treatment with of DECPR at both doses significantly reduced the colonic ACF formation compared with the positive cancer control group. Immunohistochemistry analysis showed down-regulation of PCNA and Bcl-2 proteins and up-regulation of Bax protein after administration of DECPR compared with the positive cancer control group. In addition, an increase in the levels of enzymatic antioxidants and a decrease in the malondialdehyde (MDA) level of the colon tissue homogenates were observed, suggesting the suppression of lipid peroxidation levels. These findings substantiate the usage of Curcuma purpurascens BI. in ethno- medicine against cancer. For wound healing experiment Sprague Dawley rats were randomly divided into four groups: vehicle control, HECPR (100-200 mg/ml), and positive control with excisional wound iv Created on the neck area. Wounds were topically dressed twice a day with HECPR for 20 days. On the 20th day, animals were sacrificed and immunohistochemical and histological processes including Hematoxylin & Eosin and Masson Trichrome stains were carried out. The antioxidant activity, namely catalase, glutathione peroxidase and superoxide dismutase, and MDA were measured in wound tissue homogenate. Macroscopic and microscopic analysis of wounds demonstrated a significant wound healing activity shown by HECPR at two doses (100-200 mg/ml). Treatment of wounds with HECPR caused significant surge in antioxidant activity and decrease in the MDA level of wound tissues compared with positive control. The immunohistochemical evaluation revealed conspicuous up-regulation of Hsp70 in treated wounds with HECPR, suggesting that the anti-inflammatory effect of HECPR. Furthermore, HECPR exhibited a promising wound healing potential towards excisional wound models in rats. The gastroprotective effect of hexane extract of HECPR was investigated against ethanol-induced gastric injury models in rats. The antiulcer study in rats (five groups, n=6) was performed with two doses of HECPR (200 and 400 mg/kg) and with omeprazole (20 mg/kg), as a standard antiulcer drug. Gross and histological features showed the antiulcerogenic characterizations of HECPR. There was significant suppression on the ulcer lesion index of rats pretreated with HECPR, which was comparable to the omeprazole effect. Oral administration of HECPR to rats resulted in a significant increase in the level of nitric oxide and antioxidant activity, including catalase, glutathione, and superoxide dismutase associated with attenuation in gastric acidity, and compensatory effect on the loss of gastric wall mucus. In addition, pretreatment of rats with HECPR caused significant reduction in the level of MDA (a marker for oxidative stress), which is associated with an increase in prostaglandin E2 activity. Immunohistochemical staining also demonstrated that HECPR induced the down-regulation of Bax and up-regulation of Hsp70 proteins after pretreatment. Collectively, the present results suggest that HECPR v has promising antiulcer potential, which could be attributed to its suppressive effect against oxidative damage and preservative effect toward gastric wall mucus. The current study suggests that Curcuma purpuracsens BI. Extracts are safe and have anti-cancer activity, cancer prevention, significant gastroprotective activity and excision wound-healing potential.